Mammal Diversity in Oil Palm Plantations and Forest Fragments in a Highly Modified Landscape in Southern Mexico - Knowlton, Jessie L.; Mata Zayas, Ena E.; Ripley, Andres J.; Valenzuela-Cordova, Bertha; Collado-Torres, Ricardo (Frontiers in Forests and Global Change, 2019)
Oil palm (Elaeis guineensis) plantations are one of the most rapidly expanding agroecosystems in the tropics, including Latin America. While many studies have demonstrated that large oil palm monocultures (>100 ha) are detrimental to biodiversity, including mammals, little is known about the impact of small-scale oil palm plantations, especially in the Neotropics. Here we used a camera trapping survey to compare species richness, community structure and relative abundances of mid to large-bodied terrestrial mammals in small-scale oil palm plantations (<100 ha) and secondary forest fragments within a highly modified landscape mosaic in the southeastern lowlands of Tabasco, Mexico. Contrary to our expectations, we found no differences in the overall mammal communities between the oil palm and forest fragments, including species richness or mean relative abundance. Individual species showed some apparent differences in their total detections between the two habitats, with 11 having greater detections in forest than oil palm, and only two with greater detections in oil palm. Further, oil palm sites were more similar to one another in terms of mammal community structure than the secondary forest fragments. We found that shorter distance to forest patches was related to higher mammal species richness in both forest fragments and oil palm plantations. Twelve terrestrial mammal species known to occur in forested areas in the state of Tabasco were never detected in either vegetation type in our surveys, highlighting the fact that the mammal community in this landscape had already been reduced to those species most resilient to human disturbance. Our findings suggest that small-scale oil palm plantations in this region are used at least to some degree by most mammals that are also found in the remaining secondary forest fragments in this landscape, but that access to nearby forest is important for these species. In order to recover more of the original mammal community and prevent further reductions in biodiversity, conservation priorities should center around reducing hunting pressure, allowing forest regeneration and increasing connectivity between protected areas and along waterways.